Marriage, Persons, and the Body: Thomistic Intimations in Karol WojtyŁa - Calano, Mark Joseph T (Archīum Ateneo, 2020)
Karol Wojtyła’s understanding of marriage, persons, and the body operates within an unarticulated Thomistic presumption. While Thomas Aquinas did not explore persons, the conjugal act, and the body in the same way as Wojtyła did, correlating the two thinkers is mutually beneficial. The paper thematically looks into marriage, persons, and the body. The first part discusses the concept of marriage and the conjugal act. Based on this understanding, the person is clarified using Wojtyła’s personalism and Thomas Aquinas’s composite person. The second part demonstrates the concept of the incommunicability of persons as Wojtyła articulates it and intimates Thomas Aquinas. This notion leads us to the third part of the paper, which puts together the ideas of Thomas Aquinas and Wojtyła in order to argue for the relational nature of the body.